2022
DOI: 10.3390/nu14030637
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Nutrition-Related Multivariate Biomarker for Mild Cognitive Impairment Based on the Plasma Free Amino Acid Profile

Abstract: Nutritional epidemiology has shown the importance of protein intake for maintaining brain function in the elderly population. Mild cognitive impairment (MCI) may be associated with malnutrition, especially protein intake. We explored blood-based biomarkers linking protein nutritional status with MCI in a multicenter study. In total, 219 individuals with MCI (79.5 ± 5.7 y) from 10 institutions and 220 individuals who were cognitively normal (CN, 76.3 ± 6.6 y) in four different cities in Japan were recruited. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Control participants (CN, N = 220) who received comprehensive health examinations were recruited from community-dwelling adults at four different cities across Japan (Hatoyama Town, Mitsuke City, Ashikaga City, and Kawasaki City) and from CN participants who visited Sunagawa City Medical Center ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Control participants (CN, N = 220) who received comprehensive health examinations were recruited from community-dwelling adults at four different cities across Japan (Hatoyama Town, Mitsuke City, Ashikaga City, and Kawasaki City) and from CN participants who visited Sunagawa City Medical Center ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Since this clinical study is a continuation of the previous report, the study is basically proceeding according to the protocol reported in the previous report ( 19 ). Neuropsychological assessments were conducted to evaluate cognitive function of the participants.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations